Importance and Association of Phytotherapy with Western Medicine in the Treatment of Diseases in Athieme in South-West Benin - BABADJIDE, CHARLES LAMBERT (My University, 2020)
The phenomenon of migration is an old one by which the migrants come to stisfy their needs in order to improve their conditions of life. In fact, the goal of this research is offering to throw more light in the factors that justify the migration flow of Gulmanceba in the town of Banikoara and the influence of their economic contribution to development. The methodologic procedure used is a mixed one at the same time qualitative and quantitative. The empirical datas have been analyzed with the saftwares CSPS, SPSS, word and Excel 2007 on the basis of the strategic analysis of Crozier and Friedberg (1977). For the data collection, the documentary research, the interview and observation are the technics used with other tools such as “interview guide” “questionnaire”, the “observation grill” and the digital camera. In total, 109 persons have been questioned among whom the Gulmanceba migrants, the natives and the local leaders. At the end of this research it has been noticed that the Gulmanceba are effective vectors that intervene everywhere in farming, the trading of adult rate fuel, manufactured products, loose pieces and sand extraction. All those economic activities positively impact the town's economiy.
Keywords: Banikoara; Migration flow; Gulmanceba; socio-economic.